Titanium Dioxide: Antibacterial Material - ธีรการุณวงศ์ ชลดา (KKU Science Journal, 2012)
The application of nanomaterials in the antibacterial field has emerged as a successful technology in recent years. Among the metal oxide, titanium dioxide (TiO2) has been found highly attractive due to its potential photocatalytic under ultraviolet. The antibacterial activity by using of TiO2 nanomaterials depends on the particle size, morphology, crystalline structure, phase composition, concentration and the used of doping metal ion. Generally, the antiobacteria mechanism of TiO2 involved with the hydroxyl free radical interact with amino group in the molecule of microorganism, resulting in cell membrane damage, cause cell death.